Real world aspects of palliative trifluridine plus tiperacil (TAS-102) in refractory metastatic colorectal cancer - Wallander, Mikael (J Gastrointest Oncol, 2020)
BACKGROUND: While recent randomised phase III trials show that trifluridine/tiperacil (TAS-102) may prolong life in patients with refractory metastatic colorectal cancer (rmCRC), palliative aspects on its efficacy and tolerability in real world patients need further elucidation. METHODS: A retrospective observational multicentre study was designed, including all patients with rmCRC who received TAS-102 under 2016–2019 in the South East Health Care region of Sweden. 48 patients were identified. Primary outcome was overall survival (OS) and secondary outcomes were progression-free survival (PFS), time to ECOG performance status deterioration (PSD), safety and dose reductions, admission to and duration of access to palliative care, and administration of TAS-102 in the last 30 days before death. RESULTS: Median OS, PFS, and time to PSD (a proxy for impaired quality of life) from start of TAS-102 were 6.4 months (95% CI: 4.4–8.4), 2.3 months (95% CI: 1.8–2.7) and 2.5 months (95% CI: 1.9–3.2), respectively. Following uni- and multivariable regression analyses, the number of previous treatment lines (≤2 vs. ≥3) was statistically independent for OS (median 7.8 vs. 5.3 months, P=0.05), PFS (median 2.4 vs. 1.8 months, P=0.03), and time to PSD (median 2.8 vs. 1.8 months, P=0.03). Thirty-four (71%) of the patients received reduced doses. The most common grade 3–4 toxicity was neutropenia (39%). Forty-three (90%) were admitted to GP or hospital-based home palliative care. Median time for access to any form of palliative care before death was 2.3 (95% CI: 0.5–3.2) months. Few patients (n=3, 7%) received their last dose of TAS-102 in their last 30 days of life. CONCLUSIONS: The outcome and tolerability of TAS-102 in rmCRC appear similar in a real-world context and randomised trials. The retrospective design and limited sample size preclude firm conclusions on subgroup analyses, but it appears that the prognosis is slightly better the earlier TAS-102 is introduced. Treatment durations are generally short, and early admission to a palliative care provider is recommended.